Intergenerational Cooperation at the Workplace from the Management Perspective - Živa Veingerl Čič; Simona Šarotar Žižek (Naše gospodarstvo/Our economy, 2017)
The labor market is currently experiencing employees of four generations. Each generation has different behavior patterns, attitudes, expectations, habits, and motivational mechanisms. As generational gaps play an important role in the business process, organizations have to find ways to balance the needs and views of different age groups. To overcome the negative outcomes arising from generational differences and to use the strengths of each generation, the implementation of comprehensive and proactive model of intergenerational cooperation, presented in the paper, is becoming the necessity for each organization because of the benefits.